Do single-session Epley maneuvers treat benign paroxysmal positional vertigo? - Çelik, Elif Kaya; Öner, Fatih; Akay, Hatice Güzelküçük (King Faisal Specialist Hospital and Research Centre, 2024)
BACKGROUND: Benign paroxysmal positional vertigo (BPPV) is the most common peripheral vestibular condition characterized by short-term vertigo attacks that significantly affect quality of life OBJECTIVES: Examine how well a single Epley maneuver worked in an outpatient setting for people with posterior canal benign paroxysmal positional vertigo (PC-BPPV) and whether they needed a second Dix-Hallpike maneuver. DESIGN: Prospective. SETTINGS: Otorhinolaryngology department of a tertiary care center. PATIENTS AND METHODS: Sociodemographic data, body mass index (BMI), and systemic disease history of 75 patients diagnosed with PC-BPPV were recorded, and their relationship with success rates after the modified Epley maneuver was analyzed. MAIN OUTCOME MEASURES: Detect cases that could not be repositioned with the diagnostic control Dix-Hallpike test performed 20 minutes after the modified Epley reposition maneuver in the same session in PC-BPPV patients. SAMPLE SIZE: 75 RESULTS: Of the 75 patients, 31 were male (41.3%), 44 female (58.6%) with a mean (standard deviation) age of 58.6 (15.9) years age, 54.6% had one or more chronic diseases. BMI was 30 mg/kg 2 and above in 31 patients (41.3%). The modified Epley maneuver was successful in 77.3%. No significant relationship was found between additional diseases or BMI in the patient group in whom the maneuver was unsuccessful. CONCLUSION: The success rates of repositioning maneuvers in treating patients diagnosed with PC-BPPV are high. However, more than a single maneuver is required in some resistant patients. Second diagnostic and repositioning maneuvers performed in the same session will reduce multiple hospital admissions. While it is helpful to repeat the maneuver in the patient group where it was unsuccessful, other factors causing the failure should be investigated. LIMITATIONS: Lack of follow-up results of patients after 7-10 days.
Keywords: Male; Adult; R; Middle Aged; Patient Positioning; Body Mass Index; Treatment Outcome; Medicine; Humans; Original Article; Female; Benign Paroxysmal Positional Vertigo; Prospective Studies; Physical Therapy Modalities; Aged; 3. Good health